Discourse analysis: Conversational analysis of the internal conversation in Oracle Corporation Malaysia - Marwa Marwa (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2015)
This study highlights the internal conversation which takes place in Oracle CorporationMalaysia. Through the study, it will be shown how conversational analysis is used toanalyze the transcription of a telephone conversation between Oracle staffs. The analysisof the transcriptions will apply a few basic concepts of conversational analysis; turntakingorganization, and the adjacency pair. The objective of the study is to find out howthe internal conversations takes place by focusing on the conversation itself, that is, theconversational structures spontaneously produced by people during talk ranging fromturn-taking strategies, how topics are introduced, conversation closings and so on. Bylooking in detail at such talk, we can gain a detailed understanding of how the staffs seethemselves in relation to the company that influence their daily lives.